The Important Role of Academic Supervision in Improving the Quality of Education - HM Usman; Mudhofir Mudhofir; Islah Gusmian (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
This article discusses the important role of academic supervision in improving the quality of education. Education has a key role in the development of a nation. Through education, the country can create a competent generation and have a positive impact on its future. Academic supervision is an important element in improving the quality of education. Supervision is not only concerned with teachers, but also pays attention to students, helping to build an efficient learning atmosphere. motivate students. This article explores various aspects of educational supervision, including the basic concept, meaning, scope, role, function, characteristics, objectives, principles and steps of educational supervision. This information can be an important guide in overcoming issues related to educational supervision and is useful as a reference for all people involved in the educational realm. By increasing understanding of educational supervision, it is hoped that it can strengthen the educational system and its contribution to achieving educational goals. holistically, in line with Law Number 20 of 2003 concerning the National Education System, emphasizing that educational supervision has an important role in improving the quality of education and stimulating sustainable growth.